EDUCATION OF THE DISADVANTAGED: A BOOK OF READINGS (Editors: A. Harry Paasow, Miriam Goldberg, and Abraham J. Tannenbaum) - Pedersen, Eigil (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1967)
A. Harry Paasow, Miriam Goldberg, and Abraham J. Tannenbaum, editors; Education of the Disadvantaged: A Book of Readings. New York: Holt, Rinehart and Winston, Inc., 1967. 503 pp.